PEMBERDAYAAN PETANI PENGELOLA HASIL HUTAN BUKAN KAYU DI DESA BATUDULANG KABUPATEN SUMBAWA - Muktasam Muktasam; Siti Nurjannah (Universitas Mataram, 2022)
As an agricultural country, agriculture is the mainstay in realizing development through increasing production, product quality, processing activities, and marketing. The results of research in the management of Non-Timber Forest Products (NTFPs) show the low awareness and attitude of the community in processing the products they produce. Farmers still tend to sell their products in unprocessed form. The ketak plant (Lygodium circinnatum) is not utilized, and is even considered a weed. This community service activity is intended to facilitate the learning process of farmers and rural communities about opportunities to use NTFPs such as candlenut, ginger and ketak for livelihood improvement. This activity was carried out with a study-action approach and was supported by PNBP funds from the University of Mataram, and the ACIAR Project - a collaboration between LPPM Unram, ICRAF, and the Kanoppi Team. The results of the activity show that farmers and target communities have increased their knowledge, attitudes and skills in processing NTFP products, especially candlenut, ginger, and ketak. Profitable NTFPs have grown, such as processing candlenut into peeled candlenut and candlenut oil, processing ginger into instant ginger drink, and processing crab cakes into craft products with high economic value. NTFP management groups have grown, and even these groups have been able to help increase the capacity of farmers and communities in other places such as Sabedo Village – Utan District in managing NTFPs. Community empowerment efforts must be carried out together through ongoing assistance. It is hoped that there will be more activities with a review-action approach in the future.